PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIA SMP BEER SEBA PEKANBARU - Pakpahan, Gunawan Saputra; Jalinus, Jalinus; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was using class action research. This research aims to fixed the process of learning and improve learning result in mathematics in grade VIIA of SMP Beer Seba Pekanbaru by applying the Discovery Learning model. The subject of this research were the students in the class VIIA of SMP Beer Seba Pekanbaru that consist of 16 boys and 11 girls at the second semester of academic year 2018/2019. During the learning process, there is a problem of learning that is still focused on the teacher so that students can not find the concept of learning. To solve this problem requires a learning model where students can actively discover their own learning concepts. The instruments of data collection in this research were observation sheets and students mathematics tests. The observation sheets were analyzed in desciptive narative, meanwhile the students’ mathematic tests were analyzed in statistic desciptive. Based on the analysis showed that an improvement of learning process prior to the action on the first and second cycles and improve the students’ in the second semester academic years 2018/2019. Based on the result of research, the implementation of discovery learning methods can fix the learning process and improving student’s achievement of learning mathematisc in grade VIIA of SMP Beer Seba Pekanbaru.Key Words : Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.